Pathophysiology of chronic bacterial osteomyelitis. Why do antibiotics fail so often?. Issue 898 (1st August 2000) - Ciampolini, J; Harding, K G
Abstract : In this review the pathophysiology of chronic bacterial osteomyelitis is summarised, focusing on how bacteria succeed so often in overcoming both host defence mechanisms and antibiotic agents. Bacteria adhere to bone matrix and orthopaedic implants via receptors to fibronectin and to other structural proteins. They subsequently elude host defences and antibiotics by "hiding" intracellularly, by developing a slimy coat, or by acquiring a very slow metabolic rate. The presence of an orthopaedic implant also causes a local polymorphonuclear cell defect, with decreased ability to kill phagocytosed bacteria. Osteolysis is determined locally by the interaction of bacterial surface components with immune system cells and subsequent cytokine production. The increasing development of antibiotic resistance by Staphylococcus aureus and S epidermidis will probably make conservative treatment even less successful than it is now. A close interaction between orthopaedic surgeons and physicians, with combined medical and operative treatment, is to be commended.